Tinjauan Sistematis Pemanfaatan Tanaman Pisang (Musa Paradisiaca L.) Wilayah Indonesia Sebagai Bahan Sediaan Kosmetik - Ida Erna Widyawati; Slamet Tuty; Alvianti Nuraiini (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Objective: To review the literature on the use of banana plants (Musa paradisiaca L.) in Indonesia. Method: A systematic search was carried out to identify relevant articles in 3 bases, namely (Google Scholars, research.gate, and Pubmed). Both include the product produced, how it is made, the contents of the banana plant samples and the evaluation of the product so that it can be accepted by society. Data analysis is based on a checklist prism with specified criteria Results: Five journals were selected because they included the desired review journal criteria. All types of products play an important role with different types of preparations and also different properties and ingredients. Conclusion: There are not many articles that discuss cosmetic products from banana plants, therefore this article was chosen to find out the contents of the banana plant samples. Most are from the skin of the banana, but some are also from the stem of the banana. Apart from that, one article discusses various benefits or parts of the banana plant which can be used as a basic ingredient for cosmetics. The content of secondary metabolites in banana plants, such as the main flavonoids, functions as an antioxidant which is much sought after in natural cosmetic products from this banana plant. Extraction was carried out for all preparations using the maceration method with ethanol solvent. And evaluation tests show that all articles conclude that all parts of the plant are capable of meeting standards to be formulated into cosmetic preparations.